A Biomimetic Lipid Membrane Device Reveals the Interaction of Cancer Biomarkers with Human Serum Lipidic Moieties. Issue 12 (10th December 2018) - Khalil‐Mgharbel, Abir; Polena, Helena; Dembélé, Paul K.; Hasan Sohag, Md. Mehadi; Alcaraz, Jean‐Pierre; Martin, Donald K.; Vilgrain, Isabelle
Abstract : A major problem for the detection of cancer biomarkers in plasma or serum is that common clinical practice does not require the patient to be in a fasting state. Considering that lipoproteins are the main population affected by food intake, the authors hypothesized that biomarkers could be embedded in lipid particles and thereby opens a new avenue for detection. Using the recently published biomarker, soluble VE‐cadherin (sVE), the authors tested our hypothesis using techniques of biophysics, biochemistry and the tools of nanobiotechnology on serum samples from kidney cancer patients ( n = 106). Optical density as well as contact angle measurements of serum revealed heterogeneity in the particle content of the serum samples. Isolation of the lipidic moieties by ultracentrifugation showed that sVE was detected in this compartment. Further, isolation of lipoprotein subclasses by precipitation with sodium phosphotungstate and MgCl2, showed that HDL carried the majority of sVE. Immunoprecipitation of sVE confirmed that it was associated with Apolipoprotein A1, a major compound of HDL. Using a biomimetic lipid bilayer membrane coupled with impedance spectroscopy the authors quantified, in real‐time, that the sVE adsorbed to the lipid bilayer membrane without altering its structure. Taken together, these results show for the first time a direct interaction of a cancer biomarker with lipids. The authors anticipate these results to prompt fasting for future blood tests for large‐scale studies in the biomarkers research field. Abstract : Biomarkers detection in clinical practice is impaired by the level of lipid and lipoproteins in blood. Biomimetic lipid bilayers combined with the electrical impedance spectroscopy (tBLM‐EIS) provide biosensors with wide range of applications in complex biological media. In this study, the authors use tBLM‐EIS to show that the biomarker soluble VE‐cadherin (sVE) can interact strongly with the lipid bilayer without altering its structure. This results demonstrate for the first time that a water soluble glycoprotein can be masked by lipoprotein in blood. This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visitwww.afob.org .